EFL JUNIOR HIGH SCHOOL STUDENTS’ PERCEPTION TOWARDS USING YOUTUBE IN LEARNING PROCESS OF ENGLISH LISTENING SKILLS - Galuh Putri Ramadhani; Yogi Setia Samsi (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Abstract: Choosing the right learning media can help students to get a better learning achievement. YouTube is known as the most visited video sharing and creating site in the world. This study aims to explore about students' perception towards using YouTube media in their learning process of English listening skills. Students tend to feel bored due to monotonous learning activities in the classroom without audio-visual media. This study also explored students’ perceptions on the types of videos they most prefer as a learning media in Junior high school. The subjects of this study are eighth grade students of one of junior high school in Karawang. This study used qualitative descriptive as the method. The data was collected from an online questionnaire through Google Form to make it easier to collect and analyze data. The result of this study showed that students have positive responses towards the English learning process in listening skills using YouTube. Students agree that using YouTube media as a learning tool in listening skills makes them more interested and motivated in deepening their English skills both for listening skills and speaking skills. They also recommended YouTube as an English learning media due to various video types that were provided in YouTube media.